Business Process Modeling in Consulting Companies - KISELEVA, IRINA ANATOLIEVNA; SADOVNIKOVA, NATALIA ALEKSEEVNA; KARMANOV, MIKHAIL VLADIMIROVICH; KUZNETSOV, VLADIMIR IVANOVICH (The journal of contemporary issues in business and government, 2021)
The international practice of leading companies indicates that there is no successful development and sound company performance improvement, particularly, in consulting, without a proper strategy as a complex of measures tailored to achieve the set goal. The relevance of this paper lies in that all business operations are fraught with risks and thus require the development and implementation of a strategy for the consulting company within the scope of various business units. Businesses face intense competition. Adequate decision-making requires in-depth comprehensive assessments of the situation and reliable forecasting. The main stages of strategy formulation of a consulting company are determined; strategic alternatives are identified; measures to evaluate strategic follow-up are drawn; examples of strategy development in a consulting company are provided. The objective of this paper is to analyse strategy development processes at consulting companies. The object is consulting companies and their business models.